FOSTERING TEACHERS TO BE CREATIVE AT THE AGE OF COVID 19 - Henny Yulia (Edukasi Lingua Sastra, 2021)
Pandemic of covid 19, sucessfully change education system in the world. Face to face system has already been changed to online system. There are many challenges for the tachers to use this system because not all students are ready to use this method. Online system does not become problematic problem for students in level of senior high school and university. But for the level of kindergarten, elementary and junior high school online system create new problems. Traditional teachers who are not accustomed to teaching online only give the students tasks without explaining anything. Hence the students become more and more confuse with the lesson. The purpose of this paper is to explain reasons why teachers crativities are needed in online classes, especially for traditional teachers who ought to cope with this problem. In addition, teachers have to upgrade their knowledge in order to adapt with unhappy situation. Moreover, some explanations about the strategies of online teaching are also clarified